Gynaecological Problems among Elderly Women Living in Old Age Homes of Kathmandu Valley - Shrestha, Marina Vaidya; Joshi, Sunil Kumar; Gopalakrishnan, Sampathia (Nepal Journal of Science and Technology, 2021)
Ageing is a natural process. The elderly population is increasing in Nepal.When there is presence of diseases, physical inability, and financial harshness, the elderly in Nepal have to face many problems. This study was thus conducted to assess the socio-economic milieu and spectrum of gynaecological problems among women living in old age homes of Kathmandu valley. For this a cross sectional study was conducted in 21old age homes of three districts of Kathmandu valley. In this study, they were 234 particants. Privacy and confidentiality of information about the individual were strictly maintained. One-third of the aged women living in the old age homes belonged to 70-80 years.50.9% were from outside Kathmandu valley, while 49.1% were from the valley. The elderly were mostly not visited by their relatives and friends. Most of them (74.4%) were interested in praying than other activities. Out of the total Urine samples (190), 68.4% were normal, and 9.4% had a urinary tract infection. There were only 15.6% uterine prolapse cases. Out of total, 70.9% of Pap smear report was normal, while 25.1% had inflammatory smear. This study revealed that the old age homes have become a shelter for most of elderly women. The socio-economic condition was poor. Gynaecological probems like UTI, Urinary incontinence were not high but the prolapse cases (uterine proplase, cystocele, rectocele) were remarkably high. Cervical cancer screening through Pap smear showed negative results.